Manuk Abeghyan - the Prototype in Memoirs - Galstyan, Ashot (Bulletin of Yerevan University B: Philology, 2026)
Memoir (French: mémoires) is the recollection of past events and personalities of interest. Many memorial pages have been written about Manuk Abeghyan, through the lines of which emerges the portrait of the great scientist, which is a collection of constantly changing states. In this genre, the portrait is completed by several principles, the most essential of which is perhaps the memoirist’s first impression. The authors portray the prototype’s portrait by accounting for external features, sometimes highlighting his eyes, face, cheeks, smile, gaze, voice, and so on. The prototype’s portrait is completed in several ways: by character traits, posture, mannerisms, inner qualities, and manifestations of mental processes, which are woven together with different stylistic-linguistic foundations. The author of the memoir, however, may ultimately have a subjective viewpoint. Often, the narrative of memory is constructed with difficulty due to a lack of clear recollection.